A Judges' Role in Pursuing Justice: Oliver Wendell Holmes' Sociological Jurisprudence Perspective - Saragih, Geofani Milthree (LAW FACULTY UNISSULA, 2023)
Judges, deemed God's agents for law enforcement globally, are the focus of this study, which analyzes their pivotal role in establishing justice within society. This examination adopts Oliver Wendell Holmes' Sociological Jurisprudence theory, advocating the perception of law as a mirror reflecting societal values and norms. Holmes emphasizes that judges must comprehend the social and economic context to apply the law effectively. Their interpretation should align with societal objectives, ensuring legal decisions resonate with contemporary societal realities. Judges must possess the acumen to adapt to societal shifts and discern the social implications of their rulings. This research delves into how Holmes' ideologies influence law enforcement, human rights protection, and the prevention of legal transgressions. Additionally, it traces Holmes' theories in the context of the Indonesian Judicial Power Act. Employing a juridical normative approach with a philosophical foundation, this study demonstrates the vital role of judges in upholding societal values of justice, corroborating Holmes' Sociological Jurisprudence theory. By considering the societal context, judges contribute to the development of a legal system that is equitable and responsive to societal transformations. This investigation also validates Holmes' theories' integration within the Indonesian Judicial Power Act.